Perception and image of dermatology in the German general population 2002–2014. (4th August 2017) - Augustin, M.; Eissing, L.; Elsner, P.; Strömer, K.; Schäfer, I.; Enk, A.; Reusch, M.; Kaufmann, R.
Abstract: Background: In contrast to other European countries, dermatologists in Germany provide health care for a broad spectrum of diseases of the skin and mucous membranes. Current population‐based data on the perception of dermatology were lacking to date. Objective: Analysis of the perception of dermatology from the general population's perspective with regard to utilization, satisfaction and responsibility. Methods: Nation‐wide survey on awareness, utilization, rating and image of dermatology in October 2014 through computer‐assisted telephone interviews on a representative sample of the adult general population ( n = 1015), performed by the FORSA institute. Results: Dermatologists as a medical specialist group are familiar to 88% of the population (2002: 65%), and approx. 82% of respondents underwent dermatological treatment in the past. Satisfaction with this treatment is high to very high in 80–90% of respondents. The majority (60–80%) name dermatologists as the desired primary provider of care for the largest share of common skin diseases. For allergic diseases, mucous membrane diseases, venous disorders and paediatric skin diseases, this rate is significantly below 50%. Conclusions: In Germany, dermatologists are perceived and valued as providers of care. In the case of skin cancer and chronic inflammatory skin diseases, they are experienced as primary care givers, whereas they are associated less frequently than their competence would justify with providing treatment for allergic and mucous membrane diseases and venous disorders. Further education of the general public and medical profession is required.